Information retrieval technology : 13th Asia Information Retrieval Societies Conference, AIRS 2017, Jeju Island, South Korea, November 22-24, 2017, Proceedings /: 13th Asia Information Retrieval Societies Conference, AIRS 2017, Jeju Island, South Korea, November 22-24, 2017, Proceedings. (2017) - Unknown
No abstract available